Establishment of Shariah principles on interest for late interim payment for construction works - Mohamad Hamdan, Noor Aishah; Ahmad Sarkawi, Azila; Abdullah Habib, Siti Nora Haryati (KPIJ Press, 2019)
Under the Malaysian law, the failure of an employer on making timely interim payments towards its contractor as agreed in the construction works contracts give rise to the rights of the contractor to claim for interest. The aim of this study is to establish Shariah principles based on the current practise of awarding interest to the contractors due to the said default. To achieve this, a qualitative study was conducted through thematic analysis of selected construction cases awarded in the Malaysian courts. From the analysis, Shariah principles are established by referring to the Al-Quran and As-Sunnah as well as Islamic legal maxims. It is recommended that the Shariah principles established from this study to be integrated in the provision of late interim payment charges during the formation of construction works contract to be in harmony with the Islamic teachings.